Binder composition for nonaqueous secondary battery electrodes, slurry composition for nonaqueous secondary battery electrodes, electrode for nonaqueous secondary batteries, and nonaqueous secondary battery
By using a water-soluble polymer X with a specific composition as a binder for non-aqueous secondary battery electrodes, the problems of dispersibility and flexibility were solved, the performance of the electrode composite layer was improved, and the productivity and battery characteristics of secondary batteries were enhanced.
Patent Information
- Application Number
- CN202480027468.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-08
- Filing Date
- 2024-07-23
- Publication Date
- 2025-11-21
AI Technical Summary
In the prior art, there is room for improvement in the dispersibility and flexibility of the electrode composite layer of non-aqueous secondary battery electrodes, which affects the productivity and performance of secondary batteries.
A non-aqueous secondary battery electrode binder composition using water-soluble polymer X, wherein the total content of conjugated diene monomer units and alkylene structural units is 25.0% by mass or more and 58.0% by mass or less, preferably containing hydroxyl-containing (meth)acrylate monomer units, acid-containing monomer units and hydroxyl-free (meth)acrylate monomer units, and controlling the weight-average molecular weight of the polymer within a specific range.
It improves the dispersibility of the slurry composition and the flexibility of the electrode composite layer, thereby enhancing the electrode's adhesion and the output and cycle characteristics of the secondary battery.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a binder composition for a nonaqueous secondary battery electrode, a slurry composition for a nonaqueous secondary battery electrode, an electrode for a nonaqueous secondary battery, and a nonaqueous secondary battery. BACKGROUND
[0002] Nonaqueous secondary batteries such as lithium ion secondary batteries (hereinafter, sometimes simply referred to as "secondary batteries") have characteristics of being small and light, having high energy density, and further being capable of repeated charge and discharge, and have been used in a wide range of applications. Therefore, in recent years, in order to further improve the performance of nonaqueous secondary batteries, improvements in battery components such as electrodes have been studied.
[0003] Here, an electrode for a secondary battery generally has an electrode composite material layer. Furthermore, the electrode composite material layer is formed, for example, by dispersing an electrode active material and a binder composition for a nonaqueous secondary battery electrode containing a polymer that plays a role as a binder material in a dispersion medium, applying the thus formed slurry-like composition (a slurry composition for a nonaqueous secondary battery electrode) to a current collector, and drying it.
[0004] Therefore, in recent years, in order to achieve further improvement in the performance of secondary batteries, improvements in binder compositions for forming electrode composite material layers have been attempted (for example, refer to Patent Literature 1).
[0005] For example, in Patent Literature 1, it is described that, as a dispersant for compounding with a conductive material dispersion, the following copolymer is compounded, the copolymer containing a unit from a (meth)acrylonitrile and a unit from a conjugated diene monomer, the proportion of the unit from the (meth)acrylonitrile in the copolymer being 15 to 50 mass%, and the weight average molecular weight being 5000 to 400000.
[0006] PRIOR ART DOCUMENTS
[0007] PATENT LITERATURE
[0008] Patent Literature 1: Japanese Patent Application Laid-Open No. 2020-187866. SUMMARY
[0009] PROBLEMS TO BE SOLVED BY THE INVENTION
[0010] Here, from the viewpoint of improving the productivity and performance of secondary batteries, the binder composition is required to improve the dispersibility of a slurry composition prepared using the binder composition, and to improve the flexibility of the obtained electrode composite material layer.
[0011] However, in the case of using a composition in which the above-described copolymer of the related art is compounded, there is room for improvement in terms of the dispersibility of the obtained slurry composition and the flexibility of the electrode composite material layer.
[0012] Accordingly, an object of the present application is to provide a binder composition for a nonaqueous secondary battery electrode capable of improving the dispersibility of a slurry composition and the flexibility of an electrode composite layer.
[0013] Further, an object of the present application is to provide a slurry composition for a nonaqueous secondary battery electrode which is excellent in dispersibility and capable of forming an electrode composite layer excellent in flexibility.
[0014] Furthermore, an object of the present application is to provide an electrode for a nonaqueous secondary battery having an electrode composite layer formed using the slurry composition for a nonaqueous secondary battery electrode.
[0015] Moreover, an object of the present application is to provide a nonaqueous secondary battery having the electrode for a nonaqueous secondary battery.
[0016] Approach to solving the problem
[0017] The present inventors have conducted intensive studies in order to achieve the above object. Then, the present inventors have found that if a binder composition for a nonaqueous secondary battery electrode in which a polymer X having a total content ratio of a conjugated diene monomer unit and an alkylene structural unit of 25.0 mass% or more and 58.0 mass% or less is dissolved in water is used, the dispersibility of a slurry composition and the flexibility of an electrode composite layer can be improved, thereby completing the present application.
[0018] That is, an object of the present application is to advantageously solve the above problems, and the present application is [1] a binder composition for a nonaqueous secondary battery electrode, comprising a polymer X and water, characterized in that the above polymer X is water-soluble and has a total content ratio of a conjugated diene monomer unit and an alkylene structural unit of 25.0 mass% or more and 58.0 mass% or less. Like this, the binder composition in which the polymer X having the specified composition and being water-soluble is dissolved can improve the dispersibility of a slurry composition and the flexibility of an electrode composite layer.
[0019] In addition, in the present specification, a polymer is "water-soluble" when the amount of insoluble components is less than 5.0 mass% when 0.5 g (solid content) of the polymer is dissolved in 100 g of water at a temperature of 25°C. Furthermore, the "monomer unit" of a polymer refers to "a repeating unit derived from a monomer included in a polymer obtained using the monomer". Furthermore, the content ratio of various repeating units (monomer units and structural units) in a polymer can be determined using 1 H-NMR and the like nuclear magnetic resonance (NMR) method.
[0020] [2] In the above-mentioned [1], in the binder composition for a nonaqueous secondary battery electrode, it is preferable that the above-mentioned polymer X contain 5.0% by mass or more and 25.0% by mass or less of a hydroxyl group-containing (meth)acrylate monomer unit. If the polymer X contains the hydroxyl group-containing (meth)acrylate monomer unit in the above-mentioned range, it is possible to improve the softness of the obtained electrode composite layer and to improve the output characteristics and the cycle characteristics of the obtained secondary battery.
[0021] In addition, in the present specification, (meth)acrylic acid means acrylic acid or methacrylic acid.
[0022] [3] Furthermore, in the above-mentioned [1] or [2], in the binder composition for a nonaqueous secondary battery electrode, it is preferable that the above-mentioned polymer X contain 20.0% by mass or more and 35.0% by mass or less of an acid group-containing monomer unit. If the polymer X contains the acid group-containing monomer unit in the above-mentioned range, it is possible to further improve the dispersibility of the slurry composition and the softness of the electrode composite layer.
[0023] [4] Furthermore, in any one of the above-mentioned [1] to [3], in the binder composition for a nonaqueous secondary battery electrode, it is preferable that the above-mentioned polymer X contain 10.0% by mass or more and 40.0% by mass or less of a (meth)acrylate monomer unit not containing a hydroxyl group. If the polymer X contains the (meth)acrylate monomer unit not containing a hydroxyl group in the above-mentioned range, it is possible to further improve the softness of the obtained electrode composite layer with respect to the current collector and the cycle characteristics of the obtained secondary battery.
[0024] [5] Furthermore, in any one of the above-mentioned [1] to [4], in the binder composition for a nonaqueous secondary battery electrode, it is preferable that the weight average molecular weight of the above-mentioned polymer X be 100,000 or more and 1,000,000 or less. If the weight average molecular weight of the polymer X is in the above-mentioned range, it is possible to further improve the dispersibility of the obtained slurry composition and the adhesion of the obtained electrode composite layer to the current collector.
[0025] Here, the weight average molecular weight of the polymer X can be measured according to the method described in the Examples of the present specification.
[0026] Furthermore, the object of the present application is to advantageously solve the above-mentioned problems, and the slurry composition for a nonaqueous secondary battery electrode of the present application is characterized by [6] containing an electrode active material and the binder composition for a nonaqueous secondary battery electrode of any one of the above-mentioned [1] to [5]. According to the slurry composition, it is possible to form an electrode composite layer that is excellent in dispersibility and excellent in softness.
[0027] [7] Here, the non-aqueous secondary battery electrode slurry composition of [6] above preferably further comprises a particulate polymer Y containing hydrophilic groups. If the slurry composition further comprises a particulate polymer Y containing hydrophilic groups, the dispersibility of the slurry composition and the adhesion and flexibility of the electrode composite material layer formed using the slurry composition to the current collector can be further improved.
[0028] [8] Furthermore, in the non-aqueous secondary battery electrode slurry composition described in [6] or [7] above, it is preferable that the content of the particulate polymer Y is 5% by mass or less when all the solid components contained in the non-aqueous secondary battery electrode slurry composition are taken as 100% by mass. If the content of the particulate polymer Y is within the range specified above, the dispersibility of the slurry composition, the adhesion and flexibility of the electrode composite material layer formed using the slurry composition to the current collector, and the internal resistance of the secondary battery can be reduced.
[0029] [9] Furthermore, in any of the above-mentioned [6] to [8] non-aqueous secondary battery electrode slurry compositions, the electrode active material preferably contains a lithium-containing composite metal oxide having an olivine-type structure. If olivine-type lithium iron phosphate is used as the electrode active material, the stability of the secondary battery against overcharging can be improved.
[0030]
[10] Furthermore, in any of the above-mentioned [6] to [9] non-aqueous secondary battery electrode slurry compositions, it is preferable to further include a conductive material containing at least one of a particulate conductive material and a carbon nanotube. If the slurry composition contains at least one of a particulate conductive material and a carbon nanotube as a conductive material, the internal resistance of the non-aqueous secondary battery can be reduced and the output characteristics can be further improved.
[0031] Furthermore, the object of the present invention is to advantageously solve the above-mentioned problems. The non-aqueous secondary battery electrode of the present invention is characterized in that
[11] it has an electrode composite material layer formed using the non-aqueous secondary battery electrode slurry composition described in any one of [6] to
[10] above. This non-aqueous secondary battery electrode has excellent flexibility, enabling the secondary battery to exhibit excellent battery characteristics.
[0032] Furthermore, the present invention aims to advantageously solve the above-mentioned problems. The non-aqueous secondary battery of the present invention is characterized by
[12] having the non-aqueous secondary battery electrode described in
[11] . The non-aqueous secondary battery exhibits excellent battery characteristics.
[0033] Invention Effects
[0034] According to the present invention, a binder composition for a non-aqueous secondary battery electrode is provided, which can improve the dispersibility of the slurry composition and the flexibility of the electrode composite layer.
[0035] Furthermore, according to the present invention, a slurry composition for a non-aqueous secondary battery electrode can be provided, which exhibits excellent dispersibility and is capable of forming an electrode composite material layer with excellent flexibility.
[0036] Furthermore, according to the present invention, it is possible to provide an electrode for a non-aqueous secondary battery having an electrode composite material layer formed using the non-aqueous secondary battery electrode slurry composition of the present invention.
[0037] Furthermore, according to the present invention, it is possible to provide a non-aqueous secondary battery having the electrode for a non-aqueous secondary battery of the present invention. Detailed Implementation
[0038] The embodiments of the present invention will now be described in detail.
[0039] Here, the binder composition for non-aqueous secondary battery electrodes of the present invention can be used to prepare the slurry composition for non-aqueous secondary battery electrodes of the present invention. Furthermore, the slurry composition for non-aqueous secondary battery electrodes of the present invention can be used in the manufacture of electrodes for non-aqueous secondary batteries such as lithium-ion secondary batteries. In addition, the non-aqueous secondary battery of the present invention is characterized by using the electrode for non-aqueous secondary battery of the present invention, which is formed using the slurry composition for non-aqueous secondary battery electrodes of the present invention.
[0040] (Binder composition for non-aqueous secondary battery electrodes)
[0041] The non-aqueous secondary battery electrode binder composition of the present invention comprises a water-soluble polymer X satisfying a specified composition. Here, the water-soluble polymer X satisfying the specified composition is characterized in that the total content of conjugated diene monomer units and alkylene structural units is 25.0% by mass or more and 58.0% by mass or less. Furthermore, since the non-aqueous secondary battery electrode binder composition of the present invention is formed by dissolving the water-soluble polymer X satisfying the specified composition in water, it is possible to prepare a slurry composition with excellent dispersibility, and the resulting electrode composite material layer exhibits excellent flexibility. In addition to the polymer X specified above, the non-aqueous secondary battery electrode binder composition of the present invention may optionally contain other components.
[0042] <Polymer X>
[0043] Polymer X is a water-soluble component that functions as a dispersant in slurry compositions prepared using binder compositions, effectively dispersing components such as electrode active materials and conductive materials. Furthermore, Polymer X also functions as a binder in electrode composite material layers formed using this slurry composition.
[0044] <<Composition of Polymer X>>
[0045] Polymer X requires that the total content of conjugated diene monomer units and alkylene structural units be 25.0% by mass or more and 58.0% by mass or less. Furthermore, polymer X preferably includes hydroxyl-containing (meth)acrylate monomer units, acid-containing monomer units, and (meth)acrylate monomer units without hydroxyl groups. Moreover, polymer X may optionally include other repeating units besides those described above.
[0046] [Conjugated diene monomer unit]
[0047] The conjugated diene monomer unit can be formed from a conjugated diene monomer. Examples of conjugated diene monomers include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. These can be used alone or in combination of two or more. 1,3-butadiene is particularly preferred.
[0048] [alkylene structural unit]
[0049] The alkylene structural unit is composed only of the general formula -C n H 2n -[where n is an integer greater than or equal to 2] represents a repeating unit consisting of alkylene structures. By including alkylene structural units in polymer X, the dispersibility of conductive materials in conductive material dispersions prepared using binder compositions can be improved.
[0050] The alkylene structural unit can be linear or branched. From the viewpoint of further improving the dispersibility of the conductive material in the conductive material dispersion, the alkylene structural unit is preferably linear, i.e., a linear-chain alkylene structural unit. Furthermore, the number of carbon atoms in the alkylene structural unit is preferably 4 or more (i.e., the number of carbon atoms in the above general formula -C). n H 2n - where n is an integer greater than or equal to 4).
[0051] Furthermore, there is no particular limitation on the method of introducing alkylene structural units into polymer X, and examples such as (1) or (2) are given below:
[0052] (1) A method for preparing a polymer from a monomer composition containing a conjugated diene monomer, and hydrogenating the polymer to convert the conjugated diene monomer unit into an alkylene structural unit;
[0053] (2) A method for preparing a polymer from a monomer composition containing a 1-olefin monomer.
[0054] Of these, method (1) is preferred because it is easy to manufacture polymers.
[0055] That is, the alkylene structural unit is preferably a structural unit obtained by hydrogenating (adding hydrogen) the conjugated diene monomer unit as described above (conjugated diene hydride unit).
[0056] In addition, examples of 1-olefin monomers include 1-butene and 1-hexene.
[0057] These conjugated diene monomers and 1-olefin monomers can be used alone or in combination of two or more.
[0058] Furthermore, as a conjugated diene monomer that can be used in the method described in (1) above, various conjugated diene monomers described in the item "[Conjugated diene monomer unit]" can be used, and 1,3-butadiene monomers are particularly preferred. That is, the alkylene structural unit is preferably a structural unit obtained by hydrogenating a conjugated diene monomer unit (conjugated diene hydride unit), and more preferably a structural unit obtained by hydrogenating a 1,3-butadiene unit (1,3-butadiene hydride unit). Moreover, hydrogenation can be carried out using known methods as described later.
[0059] Furthermore, when alkylene structural units are introduced into the polymer via the method described in (1) above, conjugated diene monomer units may remain in polymer X if the conjugated diene monomer units are not completely hydrogenated. In other words, polymer X can arbitrarily contain conjugated diene monomer units as repeating units.
[0060] When all repeating units (the sum of structural units and monomer units) in polymer X are taken as 100% by mass, the total content of conjugated diene monomer units and alkylene structural units in polymer X needs to be 25.0% by mass or more, preferably 27.5% by mass or more, more preferably 30.0% by mass or more, and needs to be 58.0% by mass or less, preferably 45.0% by mass or less, more preferably 40.0% by mass or less. If the total content of alkylene structural units and conjugated diene monomer units in polymer X is at or above the above-mentioned lower limit, the flexibility of the obtained electrode composite material layer and the adhesion to the current collector can be improved, resulting in improved cycle characteristics of the obtained secondary battery. Furthermore, if the total content of alkylene structural units and conjugated diene monomer units in polymer X is below the above-mentioned upper limit, the decrease in water solubility of polymer X can be suppressed, and the dispersibility of the obtained slurry composition can be improved.
[0061] Furthermore, polymer X may contain at least one of a conjugated diene monomer unit and an alkylene structural unit. If polymer X does not contain either a conjugated diene monomer unit or an alkylene structural unit, the total content ratio of the conjugated diene monomer unit and the alkylene structural unit is equal to the content ratio of the present monomer unit to the structural unit. For example, in the method described in (1) above, if the conjugated diene monomer unit is completely hydrogenated, or if the polymer is manufactured by the method described in (2) above (and, without introducing additional conjugated diene monomer units), polymer X may contain an alkylene structural unit but not a conjugated diene monomer unit. Alternatively, in the method described in (1) above, if the conjugated diene monomer unit is not completely hydrogenated, polymer X may contain both a conjugated diene monomer unit and an alkylene structural unit.
[0062] [Contains hydroxy (meth)acrylate monomer units]
[0063] Polymer X preferably further contains hydroxyl-containing (meth)acrylate monomer units, that is, at least one of hydroxyl-containing acrylate monomer units and hydroxyl-containing methacrylate monomer units. Examples of hydroxyl-containing acrylate monomers capable of forming the hydroxyl-containing acrylate monomer units in polymer X include alkyl esters of acrylic acid such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and 4-hydroxybutyl acrylate (also known as "hydroxyalkyl acrylate monomers"); general formula: CH2=CH-COO-(C q H 2q O) p -H (where p represents an integer from 2 to 9 and q represents an integer from 2 to 4) represents polyalkylene glycols and esters of acrylic acid (also known as "polyalkylene glycol ester monomers of acrylic acid"). Furthermore, these can be used alone or in any ratio of two or more.
[0064] Among them, hydroxyl-containing acrylate monomers are preferably alkyl esters of acrylic acid (hydroxyalkyl acrylate monomers) such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and 4-hydroxybutyl acrylate.
[0065] Examples of hydroxymethyl methacrylate monomers capable of forming hydroxymethyl methacrylate monomer units in polymer X include: alkyl esters of methacrylic acid such as 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate (also known as "hydroxyalkyl methacrylate monomers"); general formula: CH2=C(CH3)-COO-(C s H 2s O) r-H (where r represents an integer from 2 to 9 and s represents an integer from 2 to 4) represents polyalkylene glycols and esters of methacrylic acid (also known as "polyalkylene glycol methacrylic acid ester monomers"). Furthermore, these can be used alone or in any ratio of two or more.
[0066] Among them, hydroxymethyl methacrylate monomers such as 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate are preferred as alkyl esters of methacrylic acid (hydroxyalkyl methacrylate monomers).
[0067] When all monomer units (all repeating units) contained in polymer X are taken as 100% by mass, the content of hydroxyl (meth)acrylate monomer units in polymer X is preferably 5.0% by mass or more, more preferably 7.5% by mass or more, even more preferably 10.0% by mass or more, preferably 25.0% by mass or less, more preferably 22.5% by mass or less, and even more preferably 20.0% by mass or less. If the content of hydroxyl (meth)acrylate monomer units in polymer X is at or above the aforementioned lower limit, it is presumed that polymer X adsorbs electrode active materials and conductive materials well when preparing the slurry composition, thus improving the softness of the obtained electrode composite material layer and the adhesion to the current collector, resulting in improved cycle characteristics of the obtained secondary battery. Furthermore, if the content of hydroxyl (meth)acrylate monomer units in polymer X is at or below the aforementioned upper limit, the dispersibility of electrode active materials and conductive materials in the prepared slurry composition can be further improved, and the softness of the obtained electrode composite material layer can be further improved. As a result, the output characteristics and cycle characteristics of the obtained secondary battery can be improved.
[0068] [Monomer unit containing acidic groups]
[0069] Polymer X preferably further contains a monomer unit containing an acidic group. Examples of acidic monomers capable of forming the acidic monomer unit in polymer X include carboxylic acid monomers, sulfonic acid monomers, and phosphate monomers.
[0070] Examples of monomers containing carboxylic acid groups include monocarboxylic acids and their derivatives, dicarboxylic acids and their anhydrides, and their derivatives.
[0071] Examples of monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid.
[0072] Examples of monocarboxylic acid derivatives include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, and β-diaminoacrylic acid.
[0073] Examples of dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.
[0074] Examples of dicarboxylic acid derivatives include methyl maleic acid, dimethyl maleic acid, phenyl maleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, methyl allyl maleate, diphenyl maleate, nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate.
[0075] Examples of anhydrides that are dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.
[0076] In addition, as a monomer with a carboxylic acid group, anhydrides that generate a carboxyl group through hydrolysis can also be used.
[0077] In addition, examples include monoethyl maleate, diethyl maleate, monobutyl maleate, dibutyl maleate, monoethyl fumarate, diethyl fumarate, monobutyl fumarate, dibutyl fumarate, monocyclohexyl fumarate, dicyclohexyl fumarate, monoethyl itaconic acid, diethyl itaconic acid, monobutyl itaconic acid, and dibutyl itaconic acid, which are monoesters and diesters of α,β-ene unsaturated polycarboxylic acids.
[0078] Furthermore, in the aforementioned monomers containing carboxylic acid groups, the hydrogen atoms in the carboxylic acid groups can also be replaced by inorganic or organic ions to form inorganic or organic salts. That is, monomers containing carboxylic acid groups can also be in the form of carboxylate salts.
[0079] Examples of monomers containing sulfonic acid groups include vinyl sulfonic acid, methyl vinyl sulfonic acid, (methyl)allyl sulfonic acid, styrene sulfonic acid, ethyl (meth)acrylic acid-2-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.
[0080] Furthermore, in the sulfonic acid groups of the aforementioned monomers containing sulfonic acid groups, the hydrogen atoms can also be replaced by inorganic or organic ions to form inorganic or organic salts. That is, monomers containing sulfonic acid groups can also be in the form of sulfonates.
[0081] Examples of phosphate-containing monomers include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.
[0082] Furthermore, in the aforementioned phosphate-containing monomers, the hydrogen atom in the phosphate group can also be replaced by inorganic or organic ions to form inorganic or organic salts. That is, phosphate-containing monomers can also be in the form of phosphates.
[0083] In addition, these acidic monomers can be used alone or in any ratio of two or more.
[0084] Furthermore, from the viewpoint of further improving the adhesion of the formed electrode composite layer to the current collector, as a monomer containing an acidic group, a monomer containing a carboxylic acid group or a monomer containing a sulfonic acid group is preferred, a monomer containing a carboxylic acid group is more preferred, and methacrylic acid is even more preferred.
[0085] When all monomer units (all repeating units) contained in polymer X are taken as 100% by mass, the content of acid-containing monomer units in polymer X is preferably 20.0% by mass or more, more preferably 21.5% by mass or more, even more preferably 23.0% by mass or more, preferably 35.0% by mass or less, more preferably 32.5% by mass or less, and even more preferably 30.0% by mass or less. If the content of acid-containing monomer units in polymer X is at or above the above-mentioned lower limit, the weakening of electrostatic repulsion caused by polymer X adsorbed on electrode active materials, etc., during the preparation of the slurry composition can be suppressed, the dispersibility of the slurry composition can be improved, thereby improving the uniformity of the electrode composite material layer, and further improving the output characteristics and cycle characteristics of the obtained secondary battery. If the content of acid-containing monomer units in polymer X is at or below the above-mentioned upper limit, the hardening of polymer X can be suppressed, the flexibility of the electrode composite material layer can be improved, and the adhesion of the electrode composite material layer to the current collector can be improved. Moreover, the output characteristics and cycle characteristics of the obtained secondary battery can be improved.
[0086] [Hydroxy-free (meth)acrylate monomer units]
[0087] Polymer X preferably further contains a hydroxyl-free (meth)acrylate monomer unit. Examples of hydroxyl-free (meth)acrylate monomer units include, for instance, hydroxyl-free alkyl (meth)acrylate monomer units.
[0088] Here, alkyl methacrylate monomers that do not contain hydroxyl groups, such as methyl methacrylate, ethyl methacrylate, butyl methacrylate, and 2-ethylhexyl methacrylate, can be used as alkyl methacrylate monomers. Furthermore, one of these can be used alone, or two or more can be used in any ratio. Among these, butyl methacrylate, methyl methacrylate, and ethyl methacrylate are preferred, butyl methacrylate and ethyl methacrylate are more preferred, and butyl methacrylate is most preferred.
[0089] When all monomer units (all repeating units) contained in polymer X are taken as 100% by mass, the content of hydroxyl-free (meth)acrylate monomer units in polymer X is preferably 10.0% by mass or more, more preferably 12.5% by mass or more, even more preferably 15.0% by mass or more, preferably 40.0% by mass or less, more preferably 37.5% by mass or less, and even more preferably 35.0% by mass or less. If the content of hydroxyl-free (meth)acrylate monomer units in polymer X is at or above the above-mentioned lower limit, the flexibility of the obtained electrode composite material layer can be further improved. In addition, if the content of hydroxyl-free (meth)acrylate monomer units in polymer X is at or below the above-mentioned upper limit, excessive swelling of polymer X in the electrolyte can be effectively suppressed, and the cycle characteristics of the secondary battery can be improved.
[0090] [Other single-unit modules]
[0091] Polymer X may also include monomer units other than the various monomer units and structural units mentioned above (hereinafter referred to as "other monomer units") as repeating units.
[0092] When all repeating units (the sum of structural units and monomer units) in the polymer are taken as 100% by mass, the content of other monomer units in polymer X is preferably 5% by mass or less, more preferably 4% by mass or less, even more preferably 3% by mass or less, even more preferably 2% by mass or less, and even more preferably 1% by mass or less. Of course, the content of other monomer units in polymer X can also be 0% by mass, that is, polymer X does not contain any monomer units other than those mentioned above. If the content of other monomer units in the polymer is below the above-mentioned upper limit, the dispersibility of the slurry composition and the flexibility of the electrode composite layer can be further improved.
[0093] There are no particular limitations on the monomers that can form other monomer units; examples include nitrile-containing monomer units and aromatic vinyl monomers. Furthermore, these monomers can be used alone or in combination of two or more.
[0094] <Polymer Preparation Methods>
[0095] Furthermore, there are no particular limitations on the manufacturing method of the above polymers, and any of the methods such as solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization can be used.
[0096] Furthermore, as a polymerization method, addition polymerization methods such as ionic polymerization, free radical polymerization, and living radical polymerization can be used. Additionally, known polymerization initiators can be used as polymerization initiators.
[0097] Furthermore, during polymerization, it is preferable to use a molecular weight regulator containing sulfur groups such as thiol groups. Examples of thiol-containing compounds that can be used as molecular weight regulators include, for example, octylthiol, 2,2,4,6,6-pentamethyl-4-heptylthiol, 2,4,4,6,6-pentamethyl-2-heptylthiol, 2,3,4,6,6-pentamethyl-2-heptylthiol, 2,3,4,6,6-pentamethyl-3-heptylthiol, tert-dodecylthiol, and n-dodecylthiol, which have 8 to 12 carbon atoms; 2,2,4,6,6-pentamethyl-4-octylthiol, 2,2,4,6,6,8,8-heptamethyl-4-nonylthiol, bis(2-mercaptoethyl) sulfide, methyl 3-mercaptopropionate, and 1-butanethiol, which have thiol groups. Compounds with thiol groups having 8 to 12 carbon atoms are particularly preferred, and tert-dodecylthiol is more preferred.
[0098] Furthermore, when polymer X is manufactured using the method described in (1) above, after emulsion polymerization, the resulting unhydrogenated polymer (i.e., the polymer precursor) is hydrogenated. Hydrogenation can be performed using known hydrogenation methods such as oil-layer hydrogenation or water-layer hydrogenation. Moreover, as the catalyst used in hydrogenation, any known selective hydrogenation catalyst can be used without limitation; palladium-based catalysts and rhodium-based catalysts can be used. Two or more of these can also be used in combination.
[0099] <Properties of Polymer X>
[0100] [Weight-average molecular weight]
[0101] The weight-average molecular weight of polymer X is preferably 10,000 or more, more preferably 15,000 or more, even more preferably 20,000 or more, preferably 1,000,000 or less, more preferably 800,000 or less, and even more preferably 600,000 or less. If the weight-average molecular weight is above or below the aforementioned lower limit, the adhesion of the obtained electrode composite layer to the current collector can be improved. On the other hand, if the weight-average molecular weight of polymer X is below or below the aforementioned upper limit, the dispersibility of the slurry composition can be improved. The average molecular weight of polymer X can be controlled, for example, by adjusting the amount of a molecular weight regulator incorporated during polymerization.
[0102] [Molecular weight distribution]
[0103] The molecular weight distribution of polymer X is preferably 1.5 or more, more preferably 1.8 or more, even more preferably 2.2 or more, preferably 10 or less, more preferably 7 or less, and even more preferably 4 or less. If the molecular weight distribution is within the above range, the dispersibility of the obtained slurry composition can be further improved, and the output characteristics and cycle characteristics of the obtained secondary battery can be further improved. In addition, the molecular weight distribution of polymer X can be calculated according to the method described in the examples below.
[0104] <Solvent>
[0105] The adhesive composition may also contain an organic solvent as a solvent other than water. Examples of organic solvents include N-methylpyrrolidone (NMP), N,N-dimethylformamide, and acetone.
[0106] <Other Ingredients>
[0107] In addition to the above-mentioned components, the binder composition for non-aqueous secondary battery electrodes of the present invention may also contain reinforcing materials, leveling agents, viscosity modifiers, electrolyte additives, etc. There are no particular limitations as long as they do not affect the battery reaction, and known components, such as those described in International Publication No. 2012 / 115096, can be used. Furthermore, these components can be used individually or in combination of two or more in any ratio.
[0108] <Preparation Method of Binder Composition for Non-Aqueous Secondary Battery Electrodes>
[0109] Furthermore, the adhesive composition of the present invention can be prepared by mixing polymer X and other components in a solvent such as water using known methods.
[0110] Furthermore, for example, an aqueous solution or aqueous dispersion of polymer X obtained by the above-described preparation method of polymer X can also be directly used as the binder composition of the present invention.
[0111] Furthermore, after mixing polymer X with an electrode active material, other components such as particulate polymer Y can be added arbitrarily, thereby enabling the simultaneous preparation of the binder composition and the slurry composition described later.
[0112] (Slurry composition for non-aqueous secondary battery electrodes)
[0113] The slurry composition for non-aqueous secondary battery electrodes of the present invention is characterized by comprising an electrode active material and the binder composition for non-aqueous secondary battery electrodes described above. The slurry composition of the present invention contains the binder composition described above, and therefore can form an electrode composite material layer with excellent dispersibility and flexibility. In addition to the electrode active material and the binder composition, the slurry composition of the present invention may optionally contain particulate polymer Y, conductive materials, and other components.
[0114] The slurry composition of the present invention can be a slurry composition for a non-aqueous secondary battery positive electrode containing a positive electrode active material as an electrode active material, or a slurry composition for a non-aqueous secondary battery negative electrode containing a negative electrode active material as an electrode active material. Here, flexibility can be a particular problem in the positive electrode composite layer; therefore, from the viewpoint of further improving the flexibility of the positive electrode composite layer as the formed electrode composite layer, the slurry composition of the present invention is preferably a slurry composition for a non-aqueous secondary battery positive electrode.
[0115] The following describes in detail the case where the non-aqueous secondary battery electrode slurry composition of the present invention is a slurry composition for a lithium-ion secondary battery positive electrode, but the present invention is not limited to the following example.
[0116] <Electrode Active Material (Positive Electrode Active Material)>
[0117] Here, there are no particular limitations on the positive electrode active material used in lithium-ion secondary batteries, and known positive electrode active materials can be used. Specifically, compounds containing transition metals, such as transition metal oxides, transition metal sulfides, and composite metal oxides of lithium and transition metals, can be used as positive electrode active materials. Furthermore, examples of transition metals include Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Mo.
[0118] Examples of transition metal oxides include MnO, MnO2, V2O5, and V6O. 13 TiO2, Cu2V2O3, amorphous V2O-P2O5, amorphous MoO3, amorphous V2O5, amorphous V6O 13 wait.
[0119] Examples of transition metal sulfides include TiS2, TiS3, amorphous MoS2, and FeS.
[0120] Examples of lithium-transition metal composite oxides include lithium-containing composite metal oxides with layered structures, lithium-containing composite metal oxides with spinel-type structures, and lithium-containing composite metal oxides with olivine-type structures. Preferably, the electrode active material contains a lithium-containing composite metal oxide with an olivine-type structure. If the electrode active material contains a lithium-containing composite metal oxide with an olivine-type structure, the stability of the secondary battery against overcharging can be improved.
[0121] Examples of lithium-containing composite metal oxides with an olivine-type structure include olivine-type lithium iron phosphate (LiFePO4), olivine-type lithium manganese phosphate (LiMnPO4), and olivine-type lithium manganese iron phosphate (LiMnPO4). 1-x Fe x PO4; 0 < x < 1) etc. Liy MdPO4 represents olivine-type lithium phosphate compounds. Here, Md represents one or more transition metals with an average oxidation state of 3+, such as Mn, Fe, and Co. Furthermore, y represents a number satisfying 0 ≤ y ≤ 2. Furthermore, in Li... y In olivine-type lithium iron phosphate compounds represented by MdPO4, a portion of Md can be replaced by other metals. Examples of metals that can be substituted include Cu, Mg, Zn, V, Ca, Sr, Ba, Ti, Al, Si, B, and Mo. Furthermore, as olivine-type lithium iron phosphate, carbon-coated olivine-type lithium iron phosphate particles, in which at least a portion of the surface of the olivine-type lithium iron phosphate particles is coated with a carbon coating, can also be used.
[0122] Furthermore, the particle size of the positive electrode active material is not particularly limited and can be appropriately adjusted within a range that yields the desired effects of the present invention. For example, the average particle size of the positive electrode active material is preferably 2 μm or less. In the present invention, the average particle size of the positive electrode active material refers to the particle size D50, which is the cumulative volume calculated from the smallest diameter side in the particle size distribution (volume basis) measured by a laser diffraction particle size analyzer manufactured by Malvern Corporation.
[0123] Furthermore, when all solid components in the slurry composition are taken as 100% by mass, the content of electrode active material in the slurry composition is preferably 90% by mass or more and 99% by mass or less. If the content of electrode active material in the slurry composition is at or above the aforementioned lower limit, the energy density of the secondary battery can be improved. On the other hand, if the content of electrode active material in the slurry composition is at or below the aforementioned upper limit, the dispersibility of the slurry composition and the adhesion and flexibility of the electrode composite layer to the current collector can be sufficiently ensured.
[0124] <Adhesive Composition>
[0125] The adhesive composition of the present invention described above can be used as an adhesive composition.
[0126] The amount of binder composition added during the preparation of the slurry composition can be appropriately adjusted within a range that yields the desired effects of the present invention. For example, when all solid components contained in the slurry composition are taken as 100% by mass, the amount of binder composition added can be adjusted such that the content of polymer X is 0.1% by mass or more and 5% by mass or less, preferably 0.1% by mass or more and 3% by mass or less, and more preferably 0.1% by mass or more and 2% by mass or less. If the content of polymer X in the slurry composition is at or above the aforementioned lower limit, the dispersibility of the slurry composition and the adhesion and flexibility of the electrode composite layer to the current collector can be further improved. On the other hand, if the content of polymer X in the slurry composition is at or below the aforementioned upper limit, the internal resistance of the secondary battery can be reduced and the output characteristics improved. In addition, the slurry composition contains polymer X and any particulate polymer Y. In the slurry composition, the total content of polymer X and particulate polymer Y as an arbitrary component satisfies the same preferred content range as described above. Specifically, it is preferably 0.1% by mass or more, preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less.
[0127] <Conductive Materials>
[0128] Conductive materials are components that facilitate electrical contact between active materials in electrode composite layers.
[0129] As a conductive material, it is preferred to use at least one of carbon nanotubes and particulate conductive materials, and more preferably to use both carbon nanotubes and particulate conductive materials.
[0130] Using at least one of carbon nanotubes and particulate conductive materials as conductive materials can improve the output characteristics of the secondary battery. Furthermore, using both carbon nanotubes and particulate conductive materials as conductive materials can further improve the output characteristics of the secondary battery.
[0131] In addition, conductive materials other than carbon nanotubes and particulate conductive materials can also be used as conductive materials. For example, fibrous conductive materials other than carbon nanotubes can be used as other conductive materials.
[0132] <<Carbon Nanotubes>>
[0133] Carbon nanotubes can improve the output characteristics of secondary batteries by forming conductive pathways in the electrode composite layer. Furthermore, the use of carbon nanotubes can also improve the cycle performance and low-temperature performance of secondary batteries.
[0134] The carbon nanotube is not particularly limited as long as it is a carbon nanotube that can achieve the desired effect of the present invention (hereinafter, sometimes abbreviated as "CNT"). Depending on the type of wall, single-walled (SW) carbon nanotubes and multi-walled (MW) carbon nanotubes can be cited as examples of carbon nanotubes. Furthermore, the carbon nanotube that can be used as a conductive material can be any of single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof.
[0135] The average wall number of CNTs is preferably 10 or less, more preferably 9 or less, even more preferably 8 or less, even more preferably 2 or less, and still even more preferably 1.5 or less. If the average wall number of CNTs is below the above-mentioned upper limit, the cycle characteristics of the secondary battery can be further improved.
[0136] In addition, there is no specific lower limit for the average wall number of CNTs, which is usually above 1.
[0137] The average diameter of CNTs is preferably 0.5 nm or more, more preferably 1 nm or more, further preferably 1.5 nm or more, even more preferably 2 nm or more, even more preferably 2.5 nm or more, preferably 20 nm or less, more preferably 12 nm or less, even more preferably 8 nm or less, even more preferably 6 nm or less, and even more preferably 4 nm or less. If the average diameter of CNTs is at or above the aforementioned lower limit, the aggregation of CNTs can be sufficiently suppressed, improving the dispersibility of CNTs as a conductive material. On the other hand, if the average diameter of CNTs is below or above the aforementioned upper limit, a good conductive path can be formed in the electrode composite material layer, further improving the output characteristics of the secondary battery and further improving the cycle characteristics of the secondary battery.
[0138] The ratio of the G-band peak intensity to the D-band peak intensity (G / D ratio) in the Raman spectrum of CNTs is preferably 0.6 or higher, more preferably 1.2 or higher, even more preferably 2.1 or higher, even more preferably 3.0 or higher, and still even more preferably 3.6 or higher. If the G / D ratio of CNTs is above the lower limit mentioned above, the cycle characteristics of the secondary battery can be further improved. Furthermore, the upper limit of the G / D ratio of CNTs is not particularly limited, for example, it is 200 or lower.
[0139] The preferred BET specific surface area of CNT is 100m². 2 / g or more, preferably 200m 2 / g or more, further preferably 250m 2 / g or more, preferably 1200m 2 / g or less, more preferably 1100m 2 / g or less, more preferably 1000m 2 / g or less. If the BET specific surface area of CNTs is within the range specified above, the output characteristics of the secondary battery can be further improved. Furthermore, in this invention, the "BET specific surface area" of CNTs refers to the nitrogen adsorption specific surface area measured using the BET method.
[0140] [Manufacturing methods for carbon nanotubes]
[0141] There are no particular limitations on CNTs with the above properties, and they can be manufactured using known methods such as arc discharge, laser ablation, and super-growth.
[0142] [Content ratio in the slurry composition]
[0143] The proportion of CNTs in the slurry composition can be appropriately adjusted within a range that yields the desired effects of the present invention. For example, when all solid components contained in the slurry composition are considered as 100% by mass, it is preferably 0.01% by mass or more and 0.5% by mass or less. If the proportion of CNTs in the slurry composition is at or above the aforementioned lower limit, the internal resistance of the secondary battery can be effectively reduced, and the output characteristics of the secondary battery can be further improved. On the other hand, if the proportion of CNTs in the slurry composition is at or below the aforementioned upper limit, the flexibility of the electrode composite layer can be improved.
[0144] <<Particulate Conductive Materials>>
[0145] Particulate conductive materials are components that can function as conductive materials in electrode composite layers and improve the flexibility of the electrode composite layers.
[0146] As a particulate conductive material, there are no particular limitations as long as it has a shape other than fibrous (e.g., spherical, plate-like, etc.). Examples include carbon black (e.g., acetylene black, Ketjen black (registered trademark), furnace black, etc.) and graphene. In addition, these particulate conductive materials can be used alone or in combination of two or more in any ratio.
[0147] [Content ratio in the slurry composition]
[0148] The proportion of particulate conductive material in the slurry composition can be appropriately adjusted within a range that yields the desired effects of the present invention. For example, when all solid components contained in the slurry composition are taken as 100% by mass, it is preferably 0.1% by mass or more and 5% by mass or less. If the proportion of particulate conductive material in the slurry composition is above the aforementioned lower limit, the flexibility of the electrode composite material layer can be further improved. On the other hand, if the proportion of particulate conductive material in the slurry composition is below the aforementioned upper limit, the adhesion of the electrode composite material layer to the current collector can be improved.
[0149] <<Mixing ratio of CNTs to particulate conductive materials>>
[0150] The mixing ratio of CNTs and particulate conductive materials is not particularly limited. For example, the proportion of CNTs in the total content of CNTs and particulate conductive materials in the slurry composition is preferably 1% by mass or more, more preferably 2% by mass or more, further preferably 3% by mass or more, preferably 30% by mass or less, and more preferably 25% by mass or less. If the proportion of CNTs in the total content of CNTs and particulate conductive materials is above the aforementioned lower limit, the internal resistance of the secondary battery can be effectively reduced, and the output characteristics of the secondary battery can be further improved. On the other hand, if the proportion of CNTs in the total content of CNTs and particulate conductive materials is below the aforementioned upper limit, the flexibility of the electrode composite material layer can be improved.
[0151] <Particulate polymer Y containing hydrophilic groups>
[0152] The particulate polymer Y containing hydrophilic groups is a component that can function as a binder in the electrode composite layer together with the aforementioned polymer X. Furthermore, the particulate polymer Y is a different polymer from polymer X. Here, the particulate polymer Y is generally non-water-soluble. In this invention, "non-water-soluble" means that when 0.5 g (converted from solid content) of the polymer is dissolved in 100 g of water at 25°C, the insoluble content is 90% by mass or more. The particulate polymer Y contains hydrophilic groups, thus further improving the dispersibility of the slurry composition and the adhesion and flexibility of the formed electrode composite layer to the current collector.
[0153] Here, there is no particular limitation on the method of introducing hydrophilic groups into the particulate polymer Y. For example, a method can be adopted in which a monomer containing a hydrophilic group is used during the polymerization of the particulate polymer Y to form a monomer unit containing a hydrophilic group in the resulting particulate polymer Y.
[0154] <<Monomer units containing hydrophilic groups>>
[0155] Examples of hydrophilic monomers that can form hydrophilic monomer units in particulate polymer Y include various monomers described above, acidic monomers that can be used to introduce acidic monomer units into polymer X, and hydroxyl monomers.
[0156] As monomers containing acidic groups (such as carboxylic acid monomers, sulfonic acid monomers, and phosphate monomers), various monomers containing acidic groups that can be used to prepare the above-mentioned polymer X can be used. These can be used alone or in combination of two or more in any ratio.
[0157] As hydroxyl-containing monomers, various compounds described above as monomers capable of introducing hydroxyl (meth)acrylate monomer units into polymer X can be used, as well as other hydroxyl-containing monomers listed below.
[0158] Other hydroxyl-containing monomers include: mono(meth)acrylates of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2'-(meth)acryloyloxy phthalate and 2-hydroxyethyl-2'-(meth)acryloyloxy succinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; and alkylene glycols such as (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether, and (meth)allyl-6-hydroxyhexyl ether. Mono(meth)allyl ethers; mono(meth)allyl ethers of poly(alkylene oxide) glycols such as diethylene glycol mono(meth)allyl ether and dipropylene glycol mono(meth)allyl ether; mono(meth)allyl ethers of halogenated and hydroxyl-substituted derivatives of (poly)alkylene glycols such as glycerol mono(meth)allyl ether, (meth)allyl-2-chloro-3-hydroxypropyl ether, and (meth)allyl-2-hydroxy-3-chloropropyl ether; mono(meth)allyl ethers of polyphenols such as eugenol and isoeugenol and their halogenated derivatives; (meth)allyl-2-hydroxyethyl sulfide, (meth)allyl-2-hydroxypropyl sulfide, and (meth)allyl-2-hydroxypropyl sulfide, etc., of alkylene glycols. Furthermore, in this invention, "(meth)allyl" refers to allyl and / or methylallyl, and "(meth)acryloyl" refers to acryloyl and / or methacryloyl.
[0159] Furthermore, from the viewpoint of further improving the dispersibility of the slurry composition and the adhesion of the formed electrode composite layer to the current collector, it is preferable to use monomers containing acidic groups (such as monomers containing carboxylic acid groups, monomers containing sulfonic acid groups, and monomers containing phosphoric acid groups). From the viewpoint of further improving the adhesion of the formed electrode composite layer, it is more preferable to use monomers containing acidic groups and monomers containing hydroxyl groups, and even more preferable to use monomers containing carboxylic acid groups and monomers containing hydroxyl groups.
[0160] -Contains Proportion-
[0161] When all monomer units contained in the particulate polymer Y are taken as 100% by mass, the content of monomer units containing hydrophilic groups in the particulate polymer Y is preferably 10% by mass or less. If the content of monomer units containing hydrophilic groups in the particulate polymer Y is within the range specified above, the dispersibility of the slurry composition and the adhesion and flexibility of the formed electrode composite layer to the current collector can be further improved.
[0162] Furthermore, when the particulate polymer Y comprises both acid-containing monomer units (carboxylic acid monomer units, sulfonic acid monomer units, and phosphate monomer units, etc.) and hydroxyl-containing monomer units as hydrophilic monomer units, the content ratio of hydrophilic monomer units in the particulate polymer Y (i.e., the total content ratio of acid-containing monomer units and hydroxyl-containing monomer units) is more preferably 2% by mass or more, further preferably 3% by mass or more, more preferably 5% by mass or less, and even more preferably 4% by mass or less, when all monomer units contained in the particulate polymer Y are taken as 100% by mass. If the total content ratio of acid-containing monomer units and hydroxyl-containing monomer units in the particulate polymer Y is within the above-specified range, the dispersibility of the slurry composition and the adhesion and flexibility of the formed electrode composite material layer to the current collector can be further improved.
[0163] Furthermore, when the particulate polymer Y includes acid-containing monomer units (such as carboxylic acid monomer units, sulfonic acid monomer units, and phosphate monomer units) as hydrophilic monomer units, the proportion of acid-containing monomer units in the particulate polymer Y, taking all monomer units contained in the particulate polymer Y as 100% by mass, is preferably 0.5% by mass or more, more preferably 1% by mass or more, further preferably 1.5% by mass or more, preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2.5% by mass or less. If the proportion of acid-containing monomer units in the particulate polymer Y is at or above the aforementioned lower limit, the dispersibility of the slurry composition and the adhesion of the formed electrode composite layer to the current collector can be further improved. On the other hand, if the proportion of acid-containing monomer units in the particulate polymer Y is at or below the aforementioned upper limit, the flexibility of the formed electrode composite layer can be sufficiently ensured.
[0164] Furthermore, when the particulate polymer Y contains hydroxyl-containing monomer units as hydrophilic monomer units, the proportion of hydroxyl-containing monomer units in the particulate polymer Y, when taking all monomer units contained in the particulate polymer Y as 100% by mass, is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1.5% by mass or less. If the proportion of acidic monomer units in the particulate polymer Y is at or above the aforementioned lower limit, the flexibility of the formed electrode composite material layer can be further improved. On the other hand, if the proportion of acidic monomer units in the particulate polymer Y is at or below the aforementioned upper limit, the dispersibility of the slurry composition and the adhesion of the formed electrode composite material layer to the current collector can be sufficiently ensured.
[0165] <<Types of Particulate Polymer Y>>
[0166] Furthermore, as a particulate polymer Y containing hydrophilic groups, for example, an acrylic polymer containing hydrophilic groups or a conjugated diene polymer containing hydrophilic groups is preferably used.
[0167] - Acrylic polymers containing hydrophilic groups-
[0168] The acrylic polymer containing a hydrophilic group is a copolymer that, in addition to the aforementioned monomer units containing hydrophilic groups, also contains at least (meth)acrylate monomer units. Furthermore, the acrylic polymer containing a hydrophilic group preferably also contains aromatic vinyl monomer units. Additionally, the acrylic polymer containing a hydrophilic group may also contain monomer units other than the monomer units containing hydrophilic groups, (meth)acrylate monomer units, and aromatic vinyl monomer units.
[0169] Furthermore, the proportion of hydrophilic monomer units in the acrylic polymer containing hydrophilic groups can be within the same range as the preferred range for the proportion of hydrophilic monomer units in the polymer described above.
[0170] As (meth)acrylate monomers capable of forming (meth)acrylate monomer units in acrylic polymers containing hydrophilic groups, alkyl (meth)acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, and 2-ethylhexyl acrylate can be used. Furthermore, one of these can be used alone, or two or more can be used in any ratio.
[0171] Additionally, in this specification, "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid.
[0172] Here, when all monomer units contained in the acrylic polymer containing hydrophilic groups are taken as 100% by mass, the content ratio of (meth)acrylate monomer units in the acrylic polymer containing hydrophilic groups is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, preferably 90% by mass or less, more preferably 85% by mass or less, and further preferably 80% by mass or less. If the content ratio of (meth)acrylate monomer units in the acrylic polymer containing hydrophilic groups is within the above-specified range, the adhesion and flexibility of the formed electrode composite material layer to the current collector can be further improved.
[0173] As an aromatic vinyl monomer capable of forming aromatic vinyl monomer units in acrylic polymers containing hydrophilic groups, the aromatic vinyl monomers described later in the section on "conjugated diene polymers containing hydrophilic groups" can be used.
[0174] When all monomer units contained in the acrylic polymer containing hydrophilic groups are taken as 100% by mass, the content of aromatic vinyl monomer units in the acrylic polymer containing hydrophilic groups is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 17% by mass or more, preferably 40% by mass or less, more preferably 35% by mass or less, and even more preferably 25% by mass or less.
[0175] - Conjugated diene polymers containing hydrophilic groups -
[0176] Conjugated diene polymers containing hydrophilic groups are copolymers that contain conjugated diene monomer units in addition to the aforementioned monomer units containing hydrophilic groups.
[0177] Specific examples of conjugated diene polymers, without particular limitation, include: styrene-butadiene copolymers containing hydrophilic groups (SBR), and copolymers containing monomer units with hydrophilic groups, aromatic vinyl monomer units, and aliphatic conjugated diene monomer units; butadiene rubber containing hydrophilic groups (BR) (a copolymer containing monomer units with hydrophilic groups and butadiene units); acrylic rubber containing hydrophilic groups (NBR) (a copolymer containing monomer units with hydrophilic groups, acrylonitrile units, and butadiene units); and their hydrides, etc. These can be used individually or in any ratio of two or more.
[0178] From the viewpoint of further improving the adhesion and flexibility of the formed electrode composite layer to the current collector, copolymers containing hydrophilic groups, such as styrene-butadiene copolymers (containing hydrophilic groups SBR), are preferred.
[0179] The proportion of hydrophilic monomer units in the conjugated diene polymer containing hydrophilic groups can be within the same range as the preferred range of the proportion of hydrophilic monomer units in the polymers described above.
[0180] As conjugated diene monomer units capable of forming conjugated diene monomer units in conjugated diene polymers containing hydrophilic groups, various compounds listed above can be cited as compounds that can be used to introduce conjugated diene monomer units into polymer X. These can be used alone or in any ratio of two or more. 1,3-Butadiene is particularly preferred.
[0181] Taking all monomer units contained in the hydrophilic conjugated diene polymer as 100% by mass, the content of conjugated diene monomer units in the hydrophilic conjugated diene polymer is preferably 15% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less. If the content of conjugated diene monomer units in the hydrophilic conjugated diene polymer is within the above-specified range, the adhesion and flexibility of the formed electrode composite material layer to the current collector can be further improved.
[0182] Examples of aromatic vinyl monomers capable of forming aromatic vinyl monomer units in conjugated diene polymers containing hydrophilic groups include styrene, α-methylstyrene, vinyltoluene, and divinylbenzene. These can be used alone or in any ratio of two or more. Styrene is particularly preferred.
[0183] Taking all monomer units contained in the hydrophilic conjugated diene polymer as 100% by mass, the content of aromatic vinyl monomer units in the hydrophilic conjugated diene polymer is preferably 30% by mass or more, more preferably 45% by mass or more, even more preferably 56% by mass or more, preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably 71% by mass or less. If the content of aromatic vinyl monomer units in the hydrophilic conjugated diene polymer is within the above-specified range, the adhesion and flexibility of the formed electrode composite material layer to the current collector can be further improved.
[0184] <<Preparation Method of Particulate Polymer Y>>
[0185] There are no particular limitations on the polymerization method of the particulate polymer A; any method such as solution polymerization, suspension polymerization, bulk polymerization, or emulsion polymerization can be used. Furthermore, addition polymerization such as ionic polymerization, free radical polymerization, and living radical polymerization can be used as the polymerization reaction. Moreover, the emulsifiers, dispersants, polymerization initiators, chain transfer agents, etc., that can be used in the polymerization can be those commonly used, and their amounts can also be those commonly used.
[0186] <<Proportion of the slurry composition>>
[0187] The proportion of particulate polymer Y in the slurry composition can be appropriately adjusted within a range that yields the desired effects of the present invention. For example, when all solid components contained in the slurry composition are taken as 100% by mass, it is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1.5% by mass or less, and may also be 0% by mass, preferably 0.1% by mass or more, more preferably 0.5% by mass or more. When the slurry composition contains particulate polymer Y, if the proportion of particulate polymer Y in the slurry composition is at or above the aforementioned lower limit, the adhesion of the electrode composite layer to the current collector can be further improved. On the other hand, if the proportion of polymer Y in the slurry composition is at or below the aforementioned upper limit, the internal resistance of the secondary battery can be reduced, and the output characteristics can be further improved.
[0188] <Dispersion Medium>
[0189] Water and organic solvents listed in the above-mentioned <solvents> category can be used as dispersion media. The amount of dispersion media can be determined such that the concentration of the solid component of the conductive material dispersion is, for example, 0.1% by mass or more and 30% by mass or less.
[0190] <Other Ingredients>
[0191] Other components that can be incorporated into the slurry composition are not particularly limited, and examples can be made of the same components that can be incorporated into the binder composition of the present invention. Furthermore, other components may be used alone or in combination of two or more in any ratio.
[0192] <Method for manufacturing slurry composition>
[0193] The above-described slurry composition can be prepared by dissolving or dispersing the above-described components in a dispersion. For example, it is preferable to prepare the slurry composition of the present invention by adding a positive electrode active material, a solvent, and any other components to the above-described binder composition and mixing them by the known methods described above. Furthermore, especially when CNTs are used as a conductive material, it is preferable to perform a multi-stage mixing process after preparing a CNT dispersion by mixing CNTs, a dispersant such as carboxymethyl cellulose, and a dispersion medium, and then further mixing it with a positive electrode active material.
[0194] (Electrodes for non-aqueous secondary batteries)
[0195] The electrode of the present invention has an electrode composite material layer formed using the slurry composition of the present invention described above, and typically has a structure in which the electrode composite material layer is formed on a current collector. Therefore, the electrode composite material layer contains at least an electrode active material and polymer X, and optionally also contains particulate polymer Y and conductive materials, etc.
[0196] The electrode active material, polymer X, particulate polymer Y, and conductive material contained in the electrode composite material layer are the same components contained in the above-mentioned slurry composition. The preferred content ratio of each component is the same as the preferred content ratio of each component when all solid components contained in the slurry composition are taken as 100% by mass.
[0197] In addition, the electrode of the present invention may further have a conductive adhesive layer comprising at least a conductive material and an adhesive between the current collector and the electrode composite material layer.
[0198] Furthermore, the electrode composite material layer of the electrode of the present invention is formed using the slurry composition of the present invention, thus exhibiting excellent flexibility and enabling the secondary battery to perform excellent battery characteristics. More specifically, the electrode composite material layer of the electrode of the present invention is formed using the slurry composition of the present invention, which has excellent dispersibility, thus possessing a uniform structure. Furthermore, as described above, the electrode composite material layer of the electrode of the present invention also exhibits excellent flexibility, thus suppressing the occurrence of cracks when, for example, the electrode is wound or folded according to the shape of the secondary battery during manufacturing. Therefore, the electrode of the present invention has a uniform structure and an electrode composite material layer with fewer cracks, thereby reducing the internal resistance of the secondary battery.
[0199] <Current collector>
[0200] Materials that are both conductive and electrochemically durable can be used as current collectors. Specifically, current collectors can be made of metals such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, and platinum. Furthermore, these materials can be used alone or in combination of two or more in any ratio.
[0201] Furthermore, in the case of manufacturing an electrode having the aforementioned conductive adhesive layer between the electrode composite material layer and the current collector, a current collector with a conductive adhesive layer formed on a current collector substrate can be used as the current collector.
[0202] As a substrate for current collectors, current collectors made of, for example, the aforementioned metallic materials can be used.
[0203] There is no particular limitation on the method for forming a conductive adhesive layer on a current collector substrate. For example, a conductive adhesive layer can be formed by applying a slurry composition (also called a “conductive adhesive”) prepared by dispersing or dissolving a conductive material and an adhesive in a dispersion medium or solvent such as water, and optionally further dispersing or dissolving a dispersant, onto a current collector substrate and then drying it.
[0204] As a conductive material, there are no particular limitations; for example, conductive materials that can be contained in the above-described slurry composition can be used. Furthermore, as a binder, there are no particular limitations; particulate polymer Y that can be contained in the above-described slurry composition can be used. Moreover, as a dispersant, there are no particular limitations; known dispersants such as carboxymethyl cellulose and its salts can be used.
[0205] Furthermore, there are no particular limitations on the method for applying a conductive adhesive to a current collector substrate and the method for drying the applied conductive adhesive; known methods can be used.
[0206] <Electrode Composite Material Layer>
[0207] The electrode composite material layer is formed via a process, for example, applying a slurry composition to a current collector (coating process) and drying the slurry composition applied to the current collector (drying process).
[0208] <<Coating Process>>
[0209] There are no particular limitations on the method for applying the slurry composition to the current collector, and known methods can be used. Specifically, as coating methods, methods such as doctor blade coating, dip coating, reverse roller coating, direct roller coating, gravure printing, extrusion coating, and brush coating can be used. In this case, the slurry composition can be applied to only one side of the current collector or to both sides. Furthermore, the thickness of the slurry composition film on the current collector before drying can be appropriately set according to the thickness of the electrode composite material layer obtained after drying.
[0210] <<Drying Process>>
[0211] There are no particular limitations on the method for drying the slurry composition coated on the current collector; known methods can be used, such as drying methods using warm air, hot air, or low-humidity air; vacuum drying methods; and drying methods using irradiation with infrared rays, electron beams, etc. By drying the slurry composition coated on the current collector in this way, an electrode composite material layer can be formed on the current collector, resulting in an electrode having both a current collector and an electrode composite material layer.
[0212] In addition, after the drying process, the electrode composite material layer can be subjected to pressure treatment using a molding machine or roller press. This pressure treatment can improve the peel strength of the electrode.
[0213] (Non-aqueous secondary battery)
[0214] The secondary battery of the present invention has the electrodes described above. For example, the secondary battery of the present invention has a positive electrode, a negative electrode, a spacer, and an electrolyte, wherein at least one of the positive electrode and the negative electrode is the electrode described above. That is, the secondary battery of the present invention may have the positive electrode of the present invention as the positive electrode and a known negative electrode as the negative electrode, or the negative electrode of the present invention as the negative electrode and a known positive electrode as the positive electrode, or both the positive and negative electrodes may be electrodes of the present invention. Moreover, flexibility may be a particular problem in the positive electrode composite material layer, so from the viewpoint of further improving the flexibility of the positive electrode composite material layer as the electrode composite material layer, the secondary battery of the present invention preferably has at least the positive electrode of the present invention as the electrode.
[0215] Furthermore, the secondary battery of the present invention has the electrodes described above, thus reducing internal resistance, providing excellent output characteristics, and providing excellent cycle characteristics.
[0216] Furthermore, the following description, as an example, illustrates the case where the non-aqueous secondary battery is a lithium-ion secondary battery, but the present invention is not limited to the following example.
[0217] <Positive electrode>
[0218] There are no particular limitations on the positive electrode; it can be any electrode as described above in this invention. That is, as the positive electrode, a positive electrode having, for example, a positive electrode composite material layer formed from the slurry composition of this invention and a current collector can be used.
[0219] Furthermore, if the electrode of the present invention is not used in the positive electrode, a known positive electrode can be used as the positive electrode.
[0220] <Negative electrode>
[0221] The negative electrode is not particularly limited and can be any electrode as described in the present invention. That is, as the negative electrode, a negative electrode having, for example, a negative electrode composite material layer formed from the slurry composition of the present invention and a current collector can be used.
[0222] Furthermore, if the electrode of the present invention is not used in the negative electrode, a known negative electrode can be used as the negative electrode.
[0223] <spacer>
[0224] As a spacer, there are no particular limitations, and examples include: microporous membranes using polyolefin-based resins (polyethylene, polypropylene, polybutene, polyvinyl chloride); microporous membranes using resins such as polyethylene terephthalate, polycyclic olefins, polyethersulfone, polyamide, polyimide, polyimide amide, polyaramid, polycyclic olefins, nylon, and polytetrafluoroethylene; woven or nonwoven fabrics using polyolefin fibers; and aggregates of particles composed of insulating materials. Among these, from the perspective of being able to adjust the overall membrane thickness of the spacer, thereby increasing the ratio of electrode composite material layers in the secondary battery and increasing the capacity per unit volume, microporous membranes using polyolefin-based resins (polyethylene, polypropylene, polybutene, polyvinyl chloride) are preferred.
[0225] Electrolyte
[0226] As an electrolyte, an electrolyte formed by dissolving the electrolyte in a solvent can be used.
[0227] Here, organic solvents capable of dissolving electrolytes can be used as solvents. Specifically, preferred solvents include: carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butyl carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; and sulfur-containing compounds such as sulfolane and dimethyl sulfoxide. Mixtures of these solvents can also be used. Furthermore, known additives such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), and ethyl methyl sulfone can be added to the solvent.
[0228] Lithium salts can be used as electrolytes. Compounds described in, for example, Japanese Patent Application Publication No. 2012-204303 can be used as lithium salts. Among these lithium salts, LiPF6, LiClO4, and CF3SO3Li are preferred as electrolytes due to their high solubility in organic solvents and high degree of dissociation. Furthermore, a single electrolyte can be used, or two or more can be used in any ratio. Generally, there is a tendency that using a supporting electrolyte with a higher degree of dissociation results in higher lithium-ion conductivity; therefore, lithium-ion conductivity can be adjusted according to the type of supporting electrolyte.
[0229] Furthermore, the secondary battery of the present invention is not particularly limited and can be manufactured using known assembly methods. Specifically, the secondary battery of the present invention can be manufactured, for example, by winding the aforementioned negative electrode, positive electrode, and spacer into a battery shape as needed, folding them, placing them into a battery container, injecting electrolyte into the battery container, and sealing it. Here, in order to prevent the internal pressure of the secondary battery from rising, overcharging, discharging, etc., overcurrent protection components such as fuses and PTC elements, porous metal mesh, and conductive plates may be provided as needed. In addition, the shape of the secondary battery can be any of, for example, coin-shaped, button-shaped, sheet-shaped, cylindrical, square, or flat.
[0230] Furthermore, the battery components of a secondary battery, such as the positive electrode, negative electrode, and spacer, are typically arranged with the positive electrode connected to one side of the spacer and the negative electrode connected to the other side of the spacer. More specifically, a positive electrode composite material layer is disposed on one side of the spacer and a negative electrode composite material layer is disposed on the other side of the spacer, so that they are in contact with the spacer respectively.
[0231] Example
[0232] The present invention will now be described in detail based on embodiments, but the present invention is not limited to these embodiments. Furthermore, in the following description, unless otherwise stated, "%" and "parts" refer to quantities based on mass.
[0233] Furthermore, in polymers manufactured by copolymerizing multiple monomers, the proportion of monomer units formed by polymerizing a particular monomer in the polymer is generally consistent with the proportion (addition ratio) of that particular monomer in all monomers used in the polymerization of the polymer, unless otherwise specified. Additionally, in the case of a hydrogenated polymer, which is formed by hydrogenating a polymer containing conjugated diene monomer units, the total proportion of unhydrogenated conjugated diene monomer units and alkylene structural units that are the hydrogenated conjugated diene monomer units in the hydrogenated polymer is consistent with the proportion (addition ratio) of the conjugated diene monomer in all monomers used in the polymerization of the polymer.
[0234] In the examples and comparative examples, various measurements and evaluations were performed using the methods described below.
[0235] <Weight-average molecular weight of polymer X>
[0236] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of polymer X were determined by gel permeation chromatography (GPC) under the following conditions using a 10 mM LiBr-DMF solution as the eluent.
[0237] • Separation chromatographic column: Shodex KD-806M (manufactured by Showa Denko Corporation)
[0238] • Detector: Differential refractometer detector RID-10A (manufactured by Shimadzu Corporation)
[0239] • Flow rate of eluent: 0.3 mL / min
[0240] • Column temperature: 40℃
[0241] • Standard polymer: TSK standard polystyrene (manufactured by Tosoh Corporation)
[0242] The test sample was prepared as follows. First, polymer X was added to 5 mL of the above eluent to achieve a solids concentration of 0.45% by mass. The mixture was then stirred at 300 rpm for 30 minutes at 25°C using a magnetic stirrer. The resulting solution was filtered through a 0.22 μm membrane filter and used as the test sample.
[0243] The value of molecular weight distribution (Mw / Mn) is calculated based on the weight-average molecular weight (Mw) and number-average molecular weight (Mn) measured in accordance with the above method.
[0244] <Volume average particle size D50 of particulate polymers>
[0245] For each particulate polymer manufactured in the Examples and Comparative Examples, the volume average particle size D50 of the particulate polymer was determined by using a laser diffraction particle size distribution measuring device (Beckman Coulter, product name "LS-230") to measure the particle size distribution (volume basis) of an aqueous dispersion solution with a solid component concentration adjusted to 0.1% by mass. This volume average particle size was calculated as the particle size (μm) at which the cumulative volume from the smallest diameter side becomes 50%.
[0246] <Dispersibility of the slurry composition>
[0247] The viscosity of the positive electrode slurry composition was measured according to JIS Z8803:1991 using a Brookfield Type B viscometer (60 rpm, 25°C) as a single-cylinder rotational viscometer, and evaluated using the following criteria. In the same slurry composition, a higher concentration of solid components within the same viscosity range (1000 mPa·s to 2000 mPa·s) indicates better dispersion of the solid components contained in the slurry composition.
[0248] A: The concentration of solid components is above 60%.
[0249] B: Solid content concentration is 58% or higher but less than 60%.
[0250] C: Solid content concentration is 55% or higher but less than 58%.
[0251] D: Solid component concentration less than 55% or non-dispersible (no flowability)
[0252] <The adhesion of the electrode composite layer to the current collector>
[0253] The positive electrodes manufactured in the examples and comparative examples were cut into rectangles 1.0 cm wide and 10 cm long to serve as test pieces. After attaching transparent tape (as specified in JIS Z1522) to the side surface of the positive electrode composite layer of the test piece, the stress was measured when the transparent tape was peeled off from one end of the test piece at a speed of 50 mm / min along a 90° direction. A total of three measurements were performed, and the average value was calculated as the peel strength (N / m), which was evaluated according to the following criteria. A higher peel strength indicates better adhesion of the positive electrode composite layer and a more robust and tighter bond between the positive electrode composite layer and the current collector.
[0254] A: Peel strength is above 10 N / m
[0255] B: Peel strength is above 8.5 N / m and less than 10 N / m
[0256] C: Peel strength is ≥7 N / m and <8.5 N / m
[0257] D: Peel strength less than 7 N / m
[0258] <Flexibility of the electrode composite layer>
[0259] In the examples and comparative examples, SUS cylindrical rods (5 cmφ, 7.5 cmφ, and 10.0 cmφ) of different diameters were placed on the positive electrode composite layer of the lithium-ion secondary battery positive electrode. The positive electrode was wound around the cylindrical rod, and the presence of cracks in the positive electrode composite layer was visually evaluated. The smaller the minimum diameter of the SUS cylindrical rod that allows the positive electrode composite layer to remain unbroken when wound around the positive electrode, the better the flexibility of the positive electrode composite layer.
[0260] A: No cracking occurred in any of the cases with a diameter of 5cm, 7.5cm, and 10.0cm.
[0261] B: It fractured at a diameter of 5 cm, but did not fracture at diameters of 7.5 cm and 10.0 cm.
[0262] C: It fractured at 5cmφ and 7.5cmφ, but did not fracture at 10.0cmφ.
[0263] D: It will fracture in any of the following cases: 5cmφ, 7.5cmφ, and 10.0cmφ.
[0264] <Output Characteristics>
[0265] After the lithium-ion secondary batteries prepared in the examples and comparative examples were injected with electrolyte, they were left to stand at 25°C for 5 hours. Next, they were charged to 20% SOC (State of Charge) using a constant current method at 0.1C at 25°C, and then aged at 60°C for 12 hours. Then, they were discharged to a cell voltage of 2.6V using a constant current method at 0.2C at 25°C. Next, they were CC-CV charged at a constant current of 0.2C (upper limit cell voltage 3.6V) and CC discharged at a constant current of 0.2C to a cell voltage of 2.6V. This 0.2C charge-discharge cycle was repeated three times. The discharge capacity of the third 0.2C discharge was taken as the initial capacity CX. Then, CC-CV charged at a constant current of 0.2C (upper limit cell voltage 3.6V) and CC discharged at a constant current of 2.0C to a cell voltage of 2.6V, and the discharge capacity at this point was taken as CY. Calculate the 2.0C / 0.2C discharge capacity retention rate, expressed as (CY / CX)×100 (%), and evaluate it using the following benchmarks. A higher discharge capacity retention rate indicates better output characteristics of the lithium-ion secondary battery.
[0266] A + The discharge capacity retention rate at 2.0C / 0.2C is over 75%.
[0267] A: The capacity retention rate at 2.0C / 0.2C discharge is above 60% and below 75%.
[0268] B: 2.0C / 0.2C discharge capacity retention is above 55% and below 60%.
[0269] C: The discharge capacity retention rate at 2.0C / 0.2C is greater than 50% and less than 55%.
[0270] D: Capacity retention rate at 2.0C / 0.2C discharge is less than 50%.
[0271] <Cyclic Characteristics>
[0272] After the lithium-ion secondary batteries prepared in the examples and comparative examples were injected with electrolyte, they were left to stand at 25°C for 5 hours. Next, they were charged to 20% SOC (State of Charge) using a constant current method at 0.1C at 25°C, followed by a 12-hour aging treatment at 60°C. Then, they were discharged to 2.6V using a constant current method at 0.2C at 25°C. Next, they were CC-CV charged (upper limit: 3.6V) using a constant current, and CC discharged to 2.6V using a constant current of 0.2C. This 0.2C charge-discharge cycle was repeated three times.
[0273] Then, under conditions of 45°C, 100 cycles of CC-CV charging (upper limit battery cell voltage 3.6V) and discharge rate of 1.0C were performed at a constant current of 0.2C with a battery cell voltage of 3.60-2.60V. The discharge capacity of the first cycle is defined as X1, and the discharge capacity of the 100th cycle is defined as X2. The capacity retention rate, expressed as ΔC = (X2 / X1) × 100 (%), was calculated using discharge capacity X1 and discharge capacity X2, and evaluated using the following benchmarks. A higher value of this capacity retention rate ΔC indicates better cycle characteristics of the lithium-ion secondary battery.
[0274] A: Capacity retention rate is above 90%.
[0275] B: Capacity retention rate is above 85% and below 90%.
[0276] C: Capacity retention rate is above 80% and below 85%.
[0277] D: Capacity retention rate less than 80%
[0278] (Example 1)
[0279] <Preparation of Polymer X (Adhesive Composition)>
[0280] 200 parts of deionized water, 8.5 parts of a 30% aqueous solution of sodium dodecyl diphenyl ether sulfonate, 15 parts of 2-hydroxyethyl methacrylate (a hydroxymethyl methacrylate monomer), 27 parts of methacrylic acid (a hydroxyl-containing monomer), 23 parts of butyl acrylate (a non-hydroxyl (meth)acrylate monomer), and 0.45 parts of tert-dodecyl mercaptan (a chain transfer agent) were added sequentially to the reactor. Next, after purging the internal gas three times with nitrogen, 35 parts of 1,3-butadiene (a conjugated diene monomer) were added. The reactor was then maintained at 10°C, and 0.06 parts of cumene hydroperoxide (a polymerization initiator), a reducing agent, and an appropriate amount of chelating agent were added. The polymerization reaction continued while stirring. When the polymerization conversion reached 85%, 0.1 parts of a 10% aqueous solution of hydroquinone (a polymerization terminator) were added to terminate the polymerization reaction. Finally, residual monomers were removed using an evaporator at 80°C to obtain an aqueous dispersion of the polymer precursor. Then, the mixture is concentrated using an evaporator to a solids concentration of 40%.
[0281] Next, 8.0% NaOH aqueous solution and deionized water were added to the concentrated polymer aqueous dispersion to adjust the pH to 8.5 and the solids concentration to 8%, yielding polymer X. Polymer X is a water-soluble polymer as defined in this specification. For the obtained polymer X, the weight-average molecular weight and molecular weight distribution were obtained as described above. The results are shown in Table 1.
[0282] <Preparation of Particulate Polymer Y>
[0283] Particulate polymer Y (an acrylic polymer containing hydrophilic groups) with hydrophilic groups is prepared according to the following steps.
[0284] Add 90 parts of deion-exchanged water and 0.5 parts of sodium lauryl sulfate as an emulsifier to a 1L flask (reaction vessel) with a rubber stopper and a stirrer. Replace the gas phase with nitrogen and heat to 60°C. Then dissolve 0.3 parts of ammonium persulfate (APS) as a polymerization initiator in 20.0 parts of deion-exchanged water and add it to the flask.
[0285] On the other hand, in another container (emulsion container), 30 parts of deionized water, 0.5 parts of sodium lauryl sulfate as an emulsifier, 78.0 parts of butyl acrylate as a (meth)acrylate monomer, 2.5 parts of itaconic acid as a monomer containing a hydrophilic group, 1.0 part of 2-hydroxyethyl acrylate, and 18.5 parts of styrene as an aromatic vinyl monomer were mixed to obtain a monomer composition. This monomer composition was continuously added to the aforementioned 1L flask with a rubber stopper over 3 hours for polymerization. The reaction was carried out at 60°C during the addition. After the addition was complete, the mixture was further stirred at 80°C for 2 hours to obtain an aqueous dispersion of particulate polymer Y.
[0286] An 8% sodium hydroxide aqueous solution was added to the aqueous dispersion of the thus obtained particulate polymer Y to adjust the pH to 8, resulting in an aqueous dispersion of particulate polymer Y. Furthermore, the obtained particulate polymer Y is non-water-soluble as defined in this specification. The volume average particle size of the particulate polymer Y was measured as described above, and the result was 135 nm.
[0287] <Preparation of Cathode Slurry Composition>
[0288] 96.5 parts of olivine-type lithium iron phosphate (LiFePO4) (average particle size: 1 μm) as the positive electrode active material and 1.5 parts of acetylene black as the conductive material were mixed using a planetary mixer (15 rpm, 15 min). Then, 1.0 part (equivalent to solids) of an aqueous solution of polymer X as a binder composition and deionized water were added to adjust the solids concentration to 78%, and the mixture was further mixed using a planetary mixer (60 rpm, 50 min). Next, water was added to adjust the viscosity of the slurry composition to be in the range of 3000 mPa·s to 4000 mPa·s. Next, 1.0 part (equivalent to solids) of an aqueous dispersion of particulate polymer Y was added, and the mixture was further mixed using a planetary mixer (40 rpm, 10 min) to prepare the positive electrode slurry composition. Finally, water was added to adjust the viscosity of the slurry composition to be in the range of 1000 mPa·s to 2000 mPa·s. The dispersibility of the obtained cathode slurry composition was evaluated as described above. The results are shown in Table 1. Furthermore, the viscosity of the obtained cathode slurry composition was measured according to JIS Z 8803:1991 using a single-cylinder rotational viscometer (Brookfield Type B viscometer). The measurement conditions were: temperature: 25°C, rotation speed: 60 rpm.
[0289] <Fabrication of a Current Collector with a Conductive Adhesive Layer>
[0290] The current collector used in the manufacture of the positive electrode is a current collector with a conductive adhesive layer, which is manufactured by the method described below.
[0291] Add 70 parts of conductive carbon (graphite / acetylene black = 70 / 30 (mass ratio)) and 8 parts of carboxymethyl cellulose (Daicel 1220, manufactured by Daicel Co., Ltd.) as a dispersant, and stir at 3000 rpm for 60 minutes using a disperser. Then add 22 parts of an aqueous dispersion of particulate polymer based on the solid content, and further stir at 1500 rpm for 10 minutes using a disperser to prepare a conductive adhesive.
[0292] A conductive adhesive is applied to an aluminum foil substrate used as a current collector using a casting method at a forming speed of 20 m / min using a roller, and then dried at 80°C to form a conductive adhesive layer with a thickness of 1 μm. This results in a current collector with a conductive adhesive layer formed on the current collector substrate.
[0293] <Fabrication of the positive electrode for lithium-ion secondary batteries>
[0294] The positive electrode slurry composition obtained as described above is applied using a corner-shaped coating machine until the dried weight per unit area is 25 mg / cm².2 The conductive adhesive layer is applied to the conductive adhesive layer side of the current collector, and dried at 90°C for 20 minutes, then further dried at 120°C for 20 minutes, followed by heat treatment at 60°C for 10 hours to obtain the positive electrode raw material. This positive electrode raw material is then calendered using a roller press to produce a material with a density of 2.5 g / cm³. 3 A sheet-shaped positive electrode is formed by a positive electrode composite material layer, a conductive adhesive layer, and aluminum foil. Then, the sheet-shaped positive electrode is cut into pieces with a width of 48.0 mm and a length of 47 cm to serve as the positive electrode for lithium-ion secondary batteries.
[0295] The obtained lithium-ion secondary battery was used as the positive electrode to evaluate the adhesion and flexibility of the positive electrode composite layer to the current collector. The results are shown in Table 1.
[0296] <Fabrication of the negative electrode for lithium-ion secondary batteries>
[0297] Add 65 parts of styrene as an aromatic vinyl monomer, 35 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 2 parts of itaconic acid as an olefinic unsaturated carboxylic acid monomer, 1 part of 2-hydroxyethyl acrylate as a hydroxyl-containing monomer, 0.3 parts of tert-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of deionized water as a solvent, and 1 part of potassium persulfate as a polymerization initiator to a 5MPa pressure vessel equipped with a stirrer. Stir thoroughly and then heat to 55°C to initiate polymerization.
[0298] The reaction was terminated by cooling when the monomer consumption reached 95.0%. A 5% sodium hydroxide aqueous solution was added to the resulting aqueous dispersion containing the polymer to adjust the pH to 8. Unreacted monomers were then removed by heated vacuum distillation. Finally, the mixture was cooled to below 30°C to obtain an aqueous dispersion of the particulate polymer used as a binder material for the negative electrode.
[0299] 48.75 parts of artificial graphite and 48.75 parts of natural graphite, as negative electrode active materials, and 1 part (equivalent to the solid content) of carboxymethyl cellulose as a thickener were added to a planetary mixer. The mixture was then diluted with deionized water to a solid content concentration of 60%, and kneaded at 45 rpm for 60 minutes. Next, 1.5 parts (equivalent to the solid content) of an aqueous dispersion of the particulate polymer obtained as described above, serving as a binder for the negative electrode, were added, and kneaded at 40 rpm for 40 minutes. Then, deionized water was added to achieve a viscosity of 3000 ± 500 mPa·s (B-type viscometer, 25°C, measured at 60 rpm), thereby preparing a slurry composition for the negative electrode.
[0300] Use a corner-shaped coating machine to achieve a coating amount of 12.5 ± 0.5 mg / cm³. 2 The aforementioned negative electrode slurry composition was applied to the surface of a 15 μm thick copper foil serving as a current collector. Then, the copper foil coated with the negative electrode slurry composition was conveyed at a speed of 400 mm / min in an oven at 80°C for 2 minutes, and further conveyed in an oven at 110°C for 2 minutes, thereby drying the negative electrode slurry composition on the copper foil, resulting in a negative electrode raw material with a negative electrode composite layer formed on the current collector.
[0301] The negative electrode raw material was calendered using a roller press to produce a material with a density of 1.6 g / cm³. 3 A sheet-shaped negative electrode is formed by a negative electrode composite material layer and copper foil. Then, the sheet-shaped negative electrode is cut into pieces with a width of 50.0 mm and a length of 52 cm to serve as the negative electrode for lithium-ion secondary batteries.
[0302] <The Manufacturing of Lithium-ion Secondary Batteries>
[0303] A positive electrode and a negative electrode for a lithium-ion secondary battery, manufactured with electrode composite layers facing each other, are wound around a 20mm diameter core through a 15μm thick spacer (a microporous membrane made of polyethylene) to obtain a wound body. The wound body is then compressed in one direction at a speed of 10mm / s to a thickness of 4.5mm. Furthermore, the compressed wound body, viewed from above, is elliptical in shape, with a major-to-minor axis ratio (major axis / minor axis) of 7.7.
[0304] In addition, a 1.0 M LiPF6 solution (solvent: a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), additive: containing 2% (volume ratio) ethylene carbonate) was prepared as the electrolyte).
[0305] Then, the compressed winding body and 3.2g of electrolyte are placed inside an aluminum laminated casing. Next, nickel leads are connected to the designated location for the negative electrode of the secondary battery, and aluminum leads are connected to the designated location for the positive electrode of the lithium-ion secondary battery. The opening of the casing is then sealed using heat to obtain the lithium-ion secondary battery. This lithium-ion secondary battery is a pouch-shaped battery with a width of 35mm, a height of 60mm, and a thickness of 5mm, and its nominal capacity is 700mAh.
[0306] The output and cycle characteristics of the obtained lithium-ion secondary batteries were evaluated using the methods described above. The results are shown in Table 1.
[0307] (Example 2)
[0308] As a particulate polymer Y having hydrophilic groups, a particulate polymer prepared as described below was used, except that the same operations, measurements, and evaluations as in Example 1 were performed. The results are shown in Table 1.
[0309] <Preparation of Particulate Polymer Y>
[0310] Particulate polymer Y (a conjugated diene polymer containing hydrophilic groups) with hydrophilic groups was prepared according to the following steps.
[0311] Add 63 parts of styrene as an aromatic vinyl monomer, 34 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 2 parts of itaconic acid as a monomer containing hydrophilic groups, 1 part of 2-hydroxyethyl acrylate, 0.3 parts of tert-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of deionized water as a solvent, and 1 part of potassium persulfate as a polymerization initiator to a 5MPa pressure vessel equipped with a stirrer. Stir thoroughly and then heat to 55°C to initiate polymerization.
[0312] The reaction was terminated by cooling when the monomer consumption reached 95.0%. A 5% sodium hydroxide aqueous solution was added to the resulting aqueous dispersion containing the polymer to adjust the pH to 8. Unreacted monomers were then removed by heated vacuum distillation. The mixture was then cooled to below 30°C to obtain an aqueous dispersion of particulate polymer. The resulting particulate polymer Y is non-water-soluble as defined in this specification. The volume average particle size of particulate polymer Y was measured as described above, and the result was 150 nm.
[0313] (Example 3)
[0314] As polymer X, a particulate polymer prepared as described below was used, except that the same operations, measurements, and evaluations as in Example 1 were performed. The results are shown in Table 1.
[0315] <Preparation of Polymer X (Hydrogenated Rubber)>
[0316] First, an aqueous dispersion of the polymer precursor was obtained in the same manner as in Example 1. Then, with the palladium content relative to the weight of the solids in the obtained aqueous dispersion of the polymer precursor at 3000 ppm, the aqueous dispersion and a palladium catalyst (a solution prepared by mixing 1% palladium acetate acetone solution with an equal weight of ion-exchanged water) were added to an autoclave, and a hydrogenation reaction was carried out at a hydrogen pressure of 3 MPa and a temperature of 55°C for 3 hours to obtain an aqueous dispersion of the target polymer X (hydrogenated rubber). The contents were then allowed to return to room temperature, creating a nitrogen environment, and then concentrated using an evaporator to a solids concentration of 40%. Next, an 8.0% NaOH aqueous solution and ion-exchanged water were added to the concentrated aqueous dispersion of polymer X to adjust the pH to 8.5 and the solids concentration to 8%, yielding polymer X. Polymer X comprises units formed by the hydrogenation of monomeric units derived from 1,3-butadiene, and therefore contains alkylene structural units. Furthermore, polymer X is a water-soluble polymer as defined in this specification. For the obtained polymer X, the weight-average molecular weight and molecular weight distribution were obtained as described above. The results are shown in Table 1.
[0317] (Examples 4-11, Comparative Examples 1-2)
[0318] In preparing polymer X, the composition of the monomer composition was changed so that the composition of the resulting polymer X is as shown in Table 1. Otherwise, the same operations, measurements, and evaluations as in Example 1 were performed. The results are shown in Table 1.
[0319] In addition, the polymer prepared in Comparative Example 2 does not meet the water solubility requirement as defined in this specification.
[0320] (Example 12)
[0321] In preparing the slurry composition for the positive electrode, as described below, after preparing the CNT dispersion, the CNT dispersion was used to prepare the slurry composition for the positive electrode. Otherwise, the same operations, measurements, and evaluations as in Example 1 were performed. The results are shown in Table 1.
[0322] <Preparation of CNT Dispersion>
[0323] 0.4 parts of carbon nanotubes (BET specific surface area: 250 m²) as a conductive material were stirred using a disperser (3000 rpm, 10 minutes). 2 Carboxymethyl cellulose (Daicel 1220, manufactured by Daicel Corporation) and 0.6 parts (converted solids) of carboxymethyl cellulose (converted solids) and 99 parts of deionized water were mixed at a circumferential speed of 8 m / s for 1 hour using a bead mill with zirconia beads of 1 mm diameter to prepare a CNT dispersion with a solids concentration of 1% by mass.
[0324] <Preparation of Cathode Slurry Composition>
[0325] 96.5 parts of olivine-type lithium iron phosphate (LiFePO4) (average particle size: 1 μm) as the positive electrode active material and 1.5 parts of acetylene black as the conductive material were mixed (15 rpm, 15 min) using a planetary mixer. Then, 1.0 part (equivalent to solids) of an aqueous solution of polymer X as a binder composition and deionized water were added to adjust the solids concentration to 78%, and the mixture was further mixed using a planetary mixer (60 rpm, 50 min). Next, a CNT dispersion was added to achieve an addition amount of 0.1 parts, and the mixture was further mixed using a planetary mixer (60 rpm, 10 min). Next, water was added to adjust the viscosity of the slurry composition to be within the range of 3000 mPa·s to 4000 mPa·s. Finally, 1.0 part (equivalent to solids) of an aqueous dispersion of particulate polymer Y was added, and the mixture was further mixed using a planetary mixer (40 rpm, 10 min) to prepare the positive electrode slurry composition. Finally, water was added to adjust the viscosity of the slurry composition to be within the range of 1000 mPa·s to 2000 mPa·s. The dispersibility of the obtained cathode slurry composition was evaluated. The results are shown in Table 1. Furthermore, the viscosity of the obtained cathode slurry composition was measured according to JIS Z 8803:1991 using a single-cylinder rotational viscometer (Brookfield Type B viscometer). The measurement conditions were set as follows: temperature: 25°C, rotation speed: 60 rpm.
[0326] (Example 13)
[0327] As described below, when preparing the slurry composition for the positive electrode, no component equivalent to particulate polymer Y was incorporated. Otherwise, the same procedures, measurements, and evaluations as in Example 1 were performed. The results are shown in Table 1.
[0328] <Preparation of Cathode Slurry Composition>
[0329] 96.5 parts of olivine-type lithium iron phosphate (LiFePO4) (average particle size: 1 μm) as the positive electrode active material and 1.5 parts of acetylene black as the conductive material were mixed (15 rpm, 15 min) using a planetary mixer. Then, 2.0 parts (equivalent to the solids content) of an aqueous solution of polymer X as a binder composition and deionized water were added to adjust the solids content concentration to 78%, and the mixture was mixed again using a planetary mixer (60 rpm, 50 min). Next, water was added to adjust the viscosity of the slurry composition to be in the range of 3000 mPa·s to 4000 mPa·s. Finally, water was added to adjust the viscosity of the slurry composition to be in the range of 1000 mPa·s to 2000 mPa·s. The dispersibility of the obtained positive electrode slurry composition was evaluated. The results are shown in Table 1. In addition, when preparing the slurry composition for the positive electrode, the viscosity of the obtained slurry composition for the positive electrode was measured using a single-cylinder rotational viscometer (Brookfield Type B viscometer) according to JIS Z8803:1991. The measurement conditions were set as follows: temperature: 25°C, rotation speed: 60 rpm.
[0330] Additionally, in Table 1 shown below,
[0331] "LFP" indicates olivine-type lithium iron phosphate.
[0332] "HEMA" stands for 2-hydroxyethyl methacrylate unit.
[0333] “BD” represents the 1,3-butadiene unit.
[0334] "MAA" represents methacrylic acid unit.
[0335] “BA” represents butyl acrylate unit.
[0336] “β-HEA” represents the 2-hydroxyethyl acrylate unit.
[0337] "ACR" indicates an acrylic polymer containing hydrophilic groups.
[0338] “SBR” indicates a conjugated diene polymer containing hydrophilic groups.
[0339] "AcB" indicates acetylene black.
[0340] "CNT" stands for carbon nanotubes.
[0341] “IP” stands for isoprene unit.
[0342] [Table 1]
[0343]
[0344] As shown in Table 1, when using a water-soluble polymer X with a total content of 25.0% by mass or more and 58.0% by mass or less of conjugated diene monomer units and alkylene structural units, the dispersibility of the slurry composition and the flexibility of the electrode composite layer can be improved.
[0345] On the other hand, it can be seen that in Comparative Example 1, where the total content of conjugated diene monomer units and alkylene structural units in polymer X is less than 25.0% by mass, and in Comparative Example 2, where the total content is greater than 58.0% by mass, the dispersibility of the slurry composition and the flexibility of the electrode composite layer are poor.
[0346] Industrial availability
[0347] According to the present invention, a binder composition for a non-aqueous secondary battery electrode is provided, which can improve the dispersibility of the slurry composition and the flexibility of the electrode composite layer.
[0348] Furthermore, according to the present invention, a slurry composition for a non-aqueous secondary battery electrode can be provided, which exhibits excellent dispersibility and is capable of forming an electrode composite material layer with excellent flexibility.
[0349] Furthermore, according to the present invention, it is possible to provide an electrode for a non-aqueous secondary battery having an electrode composite material layer formed using the non-aqueous secondary battery electrode slurry composition of the present invention.
[0350] Furthermore, according to the present invention, it is possible to provide a non-aqueous secondary battery having the electrode for a non-aqueous secondary battery of the present invention.
Claims
1. A binder composition for a non-aqueous secondary battery electrode, comprising polymer X and water, The polymer X is water-soluble and contains a total of 25.0% by mass and less than 58.0% by mass of conjugated diene monomer units and alkylene structural units.
2. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The polymer X contains 5.0% by mass and less than 25.0% by mass of hydroxyl (meth)acrylate monomer units.
3. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The polymer X contains more than 20.0% by mass and less than 35.0% by mass of monomer units containing acidic groups.
4. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The polymer X contains 10.0% by mass and 40.0% by mass of hydroxyl-free (meth)acrylate monomer units.
5. The binder composition for non-aqueous secondary battery electrodes according to claim 1, wherein, The weight-average molecular weight of polymer X is above 100,000 and below 1,000,000.
6. A slurry composition for a non-aqueous secondary battery electrode, comprising an electrode active material and a binder composition for a non-aqueous secondary battery electrode according to any one of claims 1 to 5.
7. The slurry composition for non-aqueous secondary battery electrodes according to claim 6, wherein, The slurry composition for the non-aqueous secondary battery electrode also includes a particulate polymer Y containing hydrophilic groups.
8. The slurry composition for non-aqueous secondary battery electrodes according to claim 7, wherein, When all solid components in the non-aqueous secondary battery electrode slurry composition are taken as 100% by mass, the content of the particulate polymer Y is 5% by mass or less.
9. The slurry composition for non-aqueous secondary battery electrodes according to claim 8, wherein, The electrode active material contains lithium-containing composite metal oxides with an olivine-type structure.
10. The slurry composition for non-aqueous secondary battery electrodes according to claim 7, wherein, The slurry composition for the electrode of the non-aqueous secondary battery further comprises a conductive material containing at least one of particulate conductive material and carbon nanotubes.
11. An electrode for a non-aqueous secondary battery, having an electrode composite material layer formed using the slurry composition for a non-aqueous secondary battery electrode as described in claim 10.
12. A non-aqueous secondary battery having the electrode for a non-aqueous secondary battery as described in claim 11.
Citation Information
Patent Citations
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Conductive material dispersion and utilization thereof
JP2020187866A
Secondary cell negative electrode, secondary cell, slurry composition for negative electrode, and method of producing secondary cell negative electrode
WO2012115096A1